Industrial training report: Pantai Hospital Ayer Keroh (PHAK) / Iffah Nasrin Mohd Rizal - Mohd Rizal, Iffah Nasrin (Faculty of Business and Management, 2023)
The internship report provides an overview of the activities, experiences, and achievements during my internship at Pantai Hospital Ayer Kerch (PHAK). This executive summary aims to present a concise and comprehensive overview of the report, highlighting the key aspects and findings. During the internship, I was involved in a range of tasks and responsibilities, including general, monthly and ad hoc tasks. My general task includes all administrative and related HR clerical tasks. For example, scanning, data entry, photocopy etc. For an intern, there are also several responsibilities being placed on me. To illustrate, I'm responsible to assist HR officer in setting up training room for orientation, make ID badge for new hires, collecting, sorting and stamping received overtime claims. In between these tasks, I’m also been given ad hoc task like preparing for birthday gifts celebration for all employees, assisting at a job fair, assisting for appreciation Treat sponsored by the CEO, etc. There are a lot of other tasks that I have experienced while being an intern at this hospital or department specifically. The internship experience facilitated personal and professional growth, providing valuable insights and learnings, including help to improve my communication skills. It was the most impactful skill that I acquired during my internship. I believe my communication skills are enough to help me get through my internship, instead I was wrong. I have learned a lot more on the need to be a more clear and stern speaker as HR is a department where strict and leniency is balanced here. The internship provided a valuable learning opportunity, enabling me to come up with SWOT analysis for the company. Based on my observation, PHAK’s strengths are the hospital is a renowned and reputable organization, has a big financial backup, a significant number of employees, and has an advanced facility. Their weaknesses are that they are having staffing challenges, limited connectivity among employees, and they are facing a shortage of bed. Despite that, they are also exposed to various opportunities like growth in telemedicine and digital health, community engagement and CSR initiatives, medical tourism, and health insurance schemes. PHAK is also not free from threats like talent acquisition and retention, intense competition with other hospitals in the region, and last but not least is the economical threats that the industry is facing which is an economy recovering nation. In conclusion, Pantai Hospital Ayer Kerch (PHAK) has established a strong reputation in the healthcare industry due to its strategic location, commitment to quality care, and affiliation with a reputable healthcare organization. To improve further, PHAK can focus on leveraging social media, addressing staffing challenges and high turnover rates, and enhancing communication channels by consolidating departments. By implementing these strategies, PHAK can enhance its market presence, improve patient care and satisfaction, and become a leading healthcare provider in Melaka and beyond.